37. Dadas as funções f(x)=x^2-1 e g(x)=2x+1, de R em R, calcule:
A) (g º f)(2)
B) (f º g)(2)
C) (f º f)(1)
D) (g º g)(-3)
Soluções para a tarefa
Respondido por
2
A) (g º f)(x)=g(f(x))=2(x²-1)+1=2x²-1
B) (f º g)(x)=f(g(x)=(2x+1)²-1=4x²+4x
C) (f º f)(x)=f(f(x))=(x²-1)²-1=x^4-2x²
D) (g º g)(x)=2(2x+1)+1=4x+3
A) (g º f)(2)=2*2²-1=7
B) (f º g)(2)=4*2²+4*2=24
C) (f º f)(1)=1^4-2*1²=1-2=-1
D) (g º g)(-3)=4*(-3)+3=-9
B) (f º g)(x)=f(g(x)=(2x+1)²-1=4x²+4x
C) (f º f)(x)=f(f(x))=(x²-1)²-1=x^4-2x²
D) (g º g)(x)=2(2x+1)+1=4x+3
A) (g º f)(2)=2*2²-1=7
B) (f º g)(2)=4*2²+4*2=24
C) (f º f)(1)=1^4-2*1²=1-2=-1
D) (g º g)(-3)=4*(-3)+3=-9
1052jeff112:
olá, corrigi um erro na letra D, 2(2x+1)+1=4x+2+1=4x+3
Respondido por
1
f(x)=x²-1
g(x)=2x+1
a)g(f(2))
f(2)=2²-1
f(2)=4-1
f(2)=3
g(f(2))=2.3+1
g(f(2))=6+1
g(f(2))=7
B)f(g(2))
g(2)=2.2+1
g(2)=4+1
g(2)=5
f(g(2))=5²-1
f(g(2))=25-1
f(g(2))=24
C)f(f(1))
f(1)=1²-1
f(1)=1-1
f(1)=0
f(f(1))=0²-1
f(f(1))=-1
D)g(g(-3))
g(-3)=2.(-3)+1
g(-3)=-6+1
g(-3)=-5
g(g(-3))=2.(-5)+1
g(g(-3))=-10+1
g(g(-3))=-9
g(x)=2x+1
a)g(f(2))
f(2)=2²-1
f(2)=4-1
f(2)=3
g(f(2))=2.3+1
g(f(2))=6+1
g(f(2))=7
B)f(g(2))
g(2)=2.2+1
g(2)=4+1
g(2)=5
f(g(2))=5²-1
f(g(2))=25-1
f(g(2))=24
C)f(f(1))
f(1)=1²-1
f(1)=1-1
f(1)=0
f(f(1))=0²-1
f(f(1))=-1
D)g(g(-3))
g(-3)=2.(-3)+1
g(-3)=-6+1
g(-3)=-5
g(g(-3))=2.(-5)+1
g(g(-3))=-10+1
g(g(-3))=-9
Perguntas interessantes
Saúde,
8 meses atrás
Química,
8 meses atrás
Geografia,
8 meses atrás
Matemática,
1 ano atrás
História,
1 ano atrás